Knowledge Level of Safe Use of Painkillers for the Elderly in Bantarsari Bogor - Lilian Batubara; Syukrini Bahri; Zwasta Pribadi Mahardika; Taufan Putra Widodo; Muhammad Razif Akbar (Nusantara Science and Technology Proceedings, 2022)
One of the basic problems in the elderly is health problems due to degenerative process, namely the emergence of non-infectious diseases such as hypertension, arthritis, stroke, heart disease, diabetes mellitus, cancer, ect. In general, degenerative diseases are chronic and cause recurrent pain, causing a tendency to use painkiller repeatedly and prolonged. Inappropriate use of painkiller can cause various side effects such as peptic ulcer, hypertension, bleeding, kidney disturbance, ect. This activity aims to increase elderly knowledge about the use of painkiller so as to avoid unwanted side effect when consuming them. The method used in this activity is counseling about the safe use of painkiller. To measure the success of the activity, pre-test and post-test were carried out using power point media and question and answers session. Data were analyzed using the Wilcoxson test. The result showed that the number of participans in this activity was 41 elderly people. The level of knowledge of the elderly about the use of painkiller is is relatively lacking, the average value of the pre-test is 59.22 and after counseling there is an increase in knowledge with an average value of 73,17 post-test. In conclusion, there was a significant increase in knowledge with p value= 0.000 after counseling.